2020
DOI: 10.1002/pc.25692
|View full text |Cite
|
Sign up to set email alerts
|

In vitro degradation of self‐reinforced poly(lactic acid) with beta‐tricalcium phosphate composite prepared by equal channel angular pressing

Abstract: Poly(lactic acid) (PLA) and beta-tricalcium phosphate (β-TCP) are biodegradable biomaterials that can be used in the field of bone fixation. This article aims to investigate the effect of equal channel angular pressing (ECAP) on the mechanical property, physical properties and in vitro degradation behaviors of PLA/β-TCP (0, 10, and 20 wt%) composites. The bending strength of PLA, PLA/10TCP, and PLA/20TCP composites processed by ECAP were 158, 154, and 137 MPa, respectively, which is higher than its initial sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In earlier studies, a decrease in σ f (or little effect) with increasing BMS content in PLLA/BMS composites [ 32 , 85 , 90 ], as well as a positive impact of BMS content on the E f value [ 11 , 32 , 85 , 86 ], have been demonstrated. In our flexural tests, σ f of the samples PL01–PL09 decreased with an increase in BMS content ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 98%
“…In earlier studies, a decrease in σ f (or little effect) with increasing BMS content in PLLA/BMS composites [ 32 , 85 , 90 ], as well as a positive impact of BMS content on the E f value [ 11 , 32 , 85 , 86 ], have been demonstrated. In our flexural tests, σ f of the samples PL01–PL09 decreased with an increase in BMS content ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 98%
“…PLA is the most widely used biodegradable polymer used in three-dimensional (3D) printing technology as filament material. [29][30][31][32][33] PLA is also clinically approved by Food and Drug Administration (FDA, USA) for some human applications such as implantable devices. [34,35] The biocompatible and biodegradable behavior of PLA makes it a suitable biomaterial for bone screws fabrication.…”
Section: Polymer Specificationsmentioning
confidence: 99%
“…[5,6] To solve these issues, the functional organic, inorganic, or metallic fillers such as particles, whiskers, and so on were added into the PLLA matrix to enhance the mechanical and crystallization properties. [7][8][9][10][11][12][13] As Wang et al [14] reported that the addition of hemp hurd into PLA matrix can improve the flexural and impact properties. Xue et al [15] reported that the presence of polyphosphoramide-intercalated MXene can increase the impact strength but retains the tensile strength of the PLA host.…”
Section: Introductionmentioning
confidence: 99%